2017
DOI: 10.3892/ijo.2017.4132
|View full text |Cite
|
Sign up to set email alerts
|

Brain lipid-binding protein promotes proliferation and modulates cell cycle in C6 rat glioma cells

Abstract: Gliomas are the most common primary brain tumors affecting adults. Four grades of gliomas have been identified, namely, grades I–IV. Brain lipid-binding protein (BLBP), which functions in the intracellular transport of fatty acids, is expressed in all grades of human gliomas. The glioma cells that are cultured in vitro are grouped into the BLBP-positive and BLBP-negative cell lines. In the present study, we found that C6 rat glioma cells was a distinct type of BLBP-negative cell line. Our results confirmed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…Western blotting was performed according to previously reported methods ( 24 ). Briefly, following culture for 24 h, a Tissue or Cell Total Protein Extraction kit (Sangon Biotech Co., Ltd.) was used to extract total protein from cells.…”
Section: Methodsmentioning
confidence: 99%
“…Western blotting was performed according to previously reported methods ( 24 ). Briefly, following culture for 24 h, a Tissue or Cell Total Protein Extraction kit (Sangon Biotech Co., Ltd.) was used to extract total protein from cells.…”
Section: Methodsmentioning
confidence: 99%
“…The contribution of hypoxia-driven mechanisms to GSC-mediated radioresistance, as discussed by Alhaddad et al [ 40 ] resonates with the findings of Hsieh et al [ 45 ] NADPH oxidase subunit 4, identified as a mediator of cycling hypoxia-promoted radiation resistance in glioblastoma multiforme, underscores the intricate relationship between the tumor microenvironment and resistance mechanisms. The role of hypoxia in shaping the GSC phenotype adds a layer of complexity to the design of targeted therapies, necessitating strategies that account for the dynamic nature of the tumor microenvironment[ 2 , 6 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, BLBP (aka, FABPB or B-FABP) was observed to be localized primarily to astrocytes in the adult brain; thus, it has been used as a marker of mature astrocytes ( Owada et al, 2006 ). Pathologically, BLBP is expressed in glioma cells ( Tian et al, 2018 , Han et al, 2017 ), and intrinsic astrocyte heterogeneity significantly contributes to glioma pathogenesis ( Irvin et al, 2017 ). Moreover, BLBP-expressing astrocytes have also been detected in experimental autoimmune encephalomyelitis ( Kipp et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%